Reliability and Validity of Cycling Sprint Performance at Isolinear Mode Without Torque Factor: A Preliminary Study in Well-Trained Male Cyclists - Nascimento, Eduardo Marcel Fernandes; Klitzke Borszcz, Fernando; Ventura, Thiago Pereira; Caputo, Fabrizio; Guglielmo, Luiz Guilherme Antonacci; de Lucas, Ricardo Dantas (Research quarterly for exercise and sport, 2024)
Purpose: This study aimed to compare the performance-derived parameters utilizing isolinear (ISO LIN ) and isovelocity (ISO VEL ) sprint cycling modes. Method: For that, 20 male trained cyclists performed 2 sprints of 7 s on an electromagnetically braked cycle ergometer in ISO LIN and six sprints in ISO VEL mode with cadences between 90 and 180 rpm, each separated by 3-min. A linear function modeled the sprints within each mode to extrapolate maximal cadence (C MAX ) and torque (T MAX ), and a quadratic function was used to extrapolate the apex defined as optimal cadence power (OPT CAD ) and peak power output (P MAX ). Fifteen subjects performed another 4 sprints at ISO LIN mode on different days to verify the reliability. Results: The measures from the power-cadence relationship were not different between the ISO LIN and ISO VEL modes. Although significant differences were detected in the T-C relationship, T MAX was greater at ISO LIN than ISO VEL (p = .006). On the other hand, C MAX was higher at ISO VEL than ISO LIN (p < .001). The correlation between parameters was large to very large (r = 0.51 to 0.89). However, high limits of agreement were verified. The ISO LIN presented consistency during the trials, and the random errors were acceptable (CV = 5.3% to 11.5%). Conclusion: Using the power-cadence relationship, P MAX and OPT CAD could be detected similarly between the two sprint modes (ISO LIN and ISO VEL ). Thus, the findings demonstrated that a single ISO LIN sprint test could be a suitable tool for quantifying the time course of muscle fatigue during and after cycling exercises in well-trained male cyclists.